Nonconventional Fluorescent Polynorbornenes Bearing Aminosuccinimide Side Groups. Issue 24 (14th November 2017) - Xu, Jing; Luo, Dan; Yin, Xianze; Zhang, Hongwei; Wang, Luoxin; Wang, Hua
Abstract: In this contribution, a new class of fluorescent polynorbornenes containing side chains that homogeneously decorated with aminosuccinimide side groups as nonconventional chromophores is introduced. First of all, monomersM1 –M3 are synthesized in an efficient and straightforward fashion by means of Michael addition between three kinds of alkyl amines and monomer precursor1, a compound containing norbornene (polymerizable group) and maleimide (Michael acceptor) groups. Subsequently, ring‐opening metathesis polymerization ofM1 –M3 is conducted to generate polymersP1 –P3 with high molecular weights ( M n values exceeding 9800) and narrow molecular weight distributions ( Ð values no more than 1.20), respectively. Quantitative conversion of monomers and microstructural integrity of polymers are verified in all cases. Finally, thermal stability, glass transition behavior, wettability, and optical properties of polymersP1 –P3 are investigated. In particular, this new class of fluorescent polymeric materials exhibits blue emission (470–478 nm) under UV irradiation with large Stokes shifts (over 110 nm). Abstract : Fluorescent polynorbornenes containing aminosuccinimide side groups as nonconventional fluorophores are generated via ring‐opening metathesis polymerization of prefunctionalized monomers. Full monomer conversion, high microstructural fidelity, predetermined molecular weight, and narrow molecular weight distribution are realized. This new family of fluorescent polymer materials shows blue emissions (470–478 nm) under UV irradiation with large Stokes shifts (over 110 nm).